SWOT ANALYSIS TO IMPROVE THE QUALITY OF ZAKAT FUND MANAGEMENT AT BMT SIMEULEU REGENCY, INDONESIA - Fachri Rahman; Cheffy Nofiana Meuraxa; Khairunnisa Khairunnisa (Proceeding International Seminar of Islamic Studies, 2022)
Zakat management is an activity of planning, organizing, implementing and supervising the collection and distribution and utilization of zakat. Fundraising activities are based on two things. First, the funds come from donors, both individuals and companies. Second, as human donors will spend funds because of obligations as Muslim matriarchs. Given these two things, the collection can coordinate with each other in terms of services and raise funds. Zakat management is an activity of planning, organizing, implementing and supervising the collection and distribution and utilization of zakat. Fundraising is a way or process in influencing individuals or groups to participate in distributing their zakat. The purpose of raising funds is that funds are not only in the form of money, but also goods or services that have commercial value. If, in the activity of collecting zakat funds, it does not generate funds, it means that this collection activity has failed.